Frequency of Covid-19 in Pregnant Women and its Effects on Fetal and Maternal Outcome - Mehreen Yousaf Rana, Haider Abbas, Uzma Parveen, Zahra Saifuddin, Zoya Ibad, Roha Sitwat, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To determine the frequency of COVID-19 in pregnant women and its effects on feto-maternal outcomes at a tertiary care hospital. Methods: Present cross-sectional study was conducted at the department of gynae and OBS, at Ziauddin University and Hospital Karachi, from April, 2020 to August 2020. All the pregnant women at term who were admitted for delivery in maternity unit, aged more than 18 years old, and of either parity, were included. After taking written and verbal informed consent women were offered to be tested for SARS-COV2 via Nasopharyngeal PCR swab test. Those women who tested positive for the COVID-19 test were treated according to the severity of the symptoms, and asymptomatic and clinically sound patients were shifted to isolation rooms. Women who presented in spontaneous labour were treated as SARS COV2 positive for safety purposes. SPSS version 22 was used to perform the analysis, all of the data. Results: A total of 454 pregnant females were tested for SARS-CoV2 via a nasopharyngeal PCR swab test, and 12 (3%) women tested positive. Out of the 12 women testing positive, 4 were preterm births, and no significant association was found between COVID PCR being positive (p=0.00) and preterm birth (p=0.112). Five out of 12 women testing positive had an episode(s) of leaking. There was a strong association between COVID PCR being positive and episodes of leaking (p=0.001). Three out of 12 women testing positive had fetal distress, while 19 out of 454 women testing negative had fetal distress (p=0.004). There were no cases of APH or PPH reported in women testing positive; however, out of 442 women testing negative, 1 APH and 3 PPH were reported. There was no mortality in either of the patients, mother or neonate. Conclusion: As per the study conclusion, the frequency of COVID-19 among women during pregnancy was observed to be only 3%, which was significantly linked to the pneumonia, leaking, and fetal distress. Keywords: Covid-19, pregnancy, complications, mortality